Formation of information signs of unmanned aerial vehicles use efficiency - Шмельов, Ю.М. (Radiotekhnika, 2019)
The subject matter of the article is an unmanned aerial vehicle and methods for determining the effectiveness of its use. The goal of the work is formation of information signs of unmanned aerial vehicles use effectiveness. The following tasks were solved in the article: formation of information signs of the effectiveness of unmanned aerial vehicles using the mathematical apparatus of probability theory and mathematical statistics, the analysis of the survivability of unmanned aerial vehicles by developing a two-level unmanned aerial vehicle control system using a neural network control system. The following methods used are: methods of probability theory and mathematical statistics, neural network management methods. The following results were obtained: The generated informational signs of unmanned aerial vehicles use effectiveness with application of the mathematical apparatus of probability theory and mathematical statistics, which made it possible to obtain an analytical expression for determining the time of information transmission by an unmanned aerial vehicle, being the main criterion for the effectiveness of its use in a given situation. An analysis of the survivability of unmanned aerial vehicles by developing a two-level control system for an unmanned aerial vehicle using a neural network control system that allows you to increase the survivability and thereby the likelihood of completing a task by an unmanned aerial vehicle. It was determined that an essential feature of the UAV functioning processes is their randomness, which is caused by the incomplete certainty of the conditions in which these processes occur, as well as various random deviations and errors that occur during the collection of information, the generation of control signals and their execution. Thus, the result of UAV functioning is randomly and quantitatively characterized by the laws of distribution of parameters expressing this result.